Biochemical and Functional Characterization of the Trace Amine-Associated Receptor 1 (TAAR1) Agonist RO5263397 - Espinoza, Stefano; Leo, Damiana; Sotnikova, Tatyana D.; Shahid, Mohammed; Kääriäinen, Tiina M.; Gainetdinov, Raul R. (Frontiers in Pharmacology, 2018)
Trace amine-associated receptor 1 (TAAR1) is a G protein-coupled receptor (GPCR), which signals through elevating intracellular cAMP levels, and expressed in most vertebrates, including rodents and humans. In recent years, several lines of evidence indicated the role of TAAR1 in the regulation of dopaminergic system and its importance in physiological processes such as locomotion, control of emotional states and cognition. In our study, we used RO5263397, a selective TAAR1 agonist, as a tool and characterized its pharmacology in vitro in HEK293 cells and its effects in vivo in tests assessing potential antidepressant and antipsychotic actions. We found that RO5263397 not only increases cAMP levels at very low concentrations but also can induce the phosphorylation of ERK and CREB in a concentration- and time-dependent manner. Like other TAAR1 agonists, RO5263397 potently suppressed high dopamine-dependent hyperactivity in mice lacking the dopamine transporter. Moreover, RO5263397 produced a strong antidepressant-like effect in the forced swim test comparable to fluoxetine. Furthermore, the antidepressant-like activity was blocked by pretreatment with SCH23390 (dopamine D1 receptor antagonist) or NBQX (glutamate AMPA receptor antagonist) but only in part by WAY100635 (serotonin 5HT1A receptor antagonist). In conclusion, our study confirms some previous in vitro and in vivo findings in relation to the pharmacological effects of RO5263397 but more importantly provides new insight on intracellular signaling pathway and other neurotransmitter receptors modulated by TAAR1 receptor activation.